Mengeksplorasi Dampak Penanaman Nilai-Nilai Religius Terhadap Kedisiplinan Siswa: Sebuah Pendekatan Baru Dalam Pendidikan Madrasah Tsanawiyah - Mila Oktafia; Adiyono Adiyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Discipline is a very important thing to instill in a person, especially in a student. Students must be careful to be disciplined in managing time, disciplined in carrying out tasks and obligations, and disciplined in interacting with the kholiq and with fellow creatures. Religious values ​​need to be instilled in children, because religious values ​​themselves involve the concept of divinity, worship, and morals. All of that can be given early on so that these religious values ​​are able to shape the child's personality and can measure strongly and have an influence throughout his life. The approach used in this study is qualitative, in collecting data the authors use the method of observation, interviews, documentation. This research was conducted at MTs Al-Ihsan Tanah Grogot. The objectives to be achieved in this study are: 1) to find out the reality of discipline at MTs Al-Ihsan Tanah Grogot, : 2) to find out the efforts to improve student discipline through the provision of religious values ​​at MTs Al-Ihsan Tanah Grogot. The results of this study are that the discipline in MTs Al-Ihsan is good, this is evident from the results of data presentation and interviews. Whereas in an effort to increase student discipline through deepening religious values, the school has programs or activities that are directed at the subject matter above, namely the habituation of Duha prayer and recitation of the Qur'an which is carried out before the lesson activities begin.